Limites de confiança para variáveis em análises de sementes de espécies florestais - Oliveira, Fernanda de (2008)
The current paper had as objective to establish confidence limits in relation to the physical and physiological quality, aiming the quality control of the analysis of seeds of forest species. To that, there were used results of the analysis of seeds of forest species, from 1997 until 2007, raised from the archives of the Analysis Laboratory of Seeds of Agricultural Research State Foundation - FEPAGRO - located in Santa Maria, Rio Grande do Sul. The limits of reliability were constructed from an analysis of data normality and the use of evaluation criteria for Garcia (1989), Lucio (1997) and Pseudo-sigma (Costa et al., 2002). The confidence limits were effective in the establishment of a minimum acceptable value so that a plot of seeds can be commercialized, proposing that the germination values (%) inside the confidence limits very low (VL) or low (L) must be discarded, because they don´t present acceptable germination contents.